Investigating antagonistic activity of fish gut bacterial isolates against aquaculture pathogens: Short Communication - Prakash, M. P.K.; Padmanaban, D.; Loganthan, C.; Palaniswamy, K.; Krishnamoorthy, K.; Manikkam, R.; Vareeket, R.; Venugopal, G. (My University, 2024)
Aquaculture worldwide suffers significant economic losses and high fish mortality due to bacterial diseases. Antibiotics have been used extensively to combat these infections owning to the overuse of antibiotics, Drug-resistant bacteria can emerge. Studies on probiotics, which provide improved growth and disease resistance, are becoming more and more popular as an antibiotic substitute, Bacteria derived from a marine setting such as fish gut might be putative candidate for aquaculture probiont. In vitro antagonistic activity against fish pathogens has been used to assess the antimicrobial properties of bacteria isolated from the gut of Sardinella longiceps and Rastrelliger Kanagurta.
Keywords: Antibiotic; Aquaculture; Fish health; Probiotics